Pharmaceutical Side Effects and Mental Health Paradoxes among Racial-Ethnic Minorities. (March 2020) - Schnittker, Jason; Do, Duy
Sociologists have long struggled to explain the minority mental health paradox: that racial-ethnic minorities often report better mental health than non-Hispanic whites despite social environments that seem less conducive to well-being. Using data from the 2008–2013 Medical Expenditure Panel Survey (MEPS), this study provides a partial explanation for the paradox rooted in a very different disparity. Evidence from MEPS indicates that non-Hispanic whites consume more pharmaceuticals than racial-ethnic minorities for a wide variety of medical conditions. Moreover, non-Hispanic whites consume more pharmaceuticals that although effective in treating their focal indication, include depression or suicide as a side effect. In models that adjust for the use of such medications, the minority advantage in significant distress is reduced, in some instances to statistical nonsignificance. Although a significant black and Hispanic advantage in a continuous measure of distress remains, the magnitude of the difference is reduced considerably. The relationship between the use of medications with suicide as a side effect and significant distress is especially large, exceeding, for instance, the relationship between poverty and significant distress. For some minority groups, the less frequent use of such medications is driven by better health (as in the case of Asians), whereas for others, it reflects a treatment disparity (as in the case of blacks), although the consequences for the mental health paradox are the same. The implications of the results are discussed, especially with respect to the neglect of psychological side effects in the treatment of physical disease as well as the problem of multiple morbidities.